BONE METASTASES OF BREAST CANCER – THE INFLUENCE OF HORMONE AND HER2 RECEPTORS - Rajković, Stanislav (Medicinski podmladak, 2023)
Breast cancer is the leading cause of cancer-related deaths among women worldwide. While significant progress has been made in the prophylaxis, diagnosis, and management of breast cancer, around 90% of deaths occur due to metastatic disease, which is still incurable. The bone has been identified as one of the predominant metastatic sites, accounting for around 80% of patients with metastatic breast cancer. The paper aims to summarize the hallmarks of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) influence on breast cancer bone metastases development and their further biological and clinical behavior.Various clinicopathological characteristics have been identified as risk factors for the development of metastases. In particular, the status of ER, PR and HER2 is crucial for making clinical decisions as an important tool for predicting the spread of breast cancer and choosing a therapeutic protocol. Patients with any hormone receptor positive status, particularly those with ER+, PR+/HER2-, are more likely to develop bone-only-metastatic (BOM), whereas those with hormone receptor negative status, especially those with so-called triple-negative (HR-/HER2-) or HER2+ breast cancer, have a predilection for visceral metastases. The paper highlights that while bone metastases of breast cancer are much less investigated than primary tumors, more studies are needed to understand the complex, multi-step process involved in the development and behavior of bone metastases.
Keywords: Breast cancer; Metastasis; Bone metastases; Hormone receptors; HER2